Effect of Abvd Chemotherapy with and without Mantle or Mediastinal Irradiation on Pulmonary Function and Symptoms in Early-Stage Hodgkin's Disease - Hirsch, A. (Institutional Knowledge at Singapore Management University, 1996)
To evaluate the effect of doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD) chemotherapy alone and of ABVD with mantle or mediastinal irradiation (RT) on the pulmonary function of patients with early-stage Hodgkin's disease. PATIENTS AND METHODS: Between 1989 and 1993, 60 patients with clinical stage I to IIIA HD enrolled onto randomized trials at Memorial Sloan-Kettering Cancer Center (MSKCC) underwent prospective evaluation of pulmonary function. All patients received six cycles of ABVD, and 30 patients received mantle or mediastinal RT. Pulmonary function tests (PFTs) and symptom evaluation were conducted before, during, and after completion of chemotherapy and RT, and at various intervals thereafter. The median follow-up time was 30 months. RESULTS: During chemotherapy, symptoms of cough and dyspnea on exertion developed in 32 of 60 patients (53%) and declines in pulmonary function occurred in 22 of 60 patients (37%). Discontinuation of bleomycin was necessary in 14 of 60 patients (23%). Following chemotherapy, there was a significant decline in median forced vital capacity (FVC) and diffusing capacity of carbon monoxide (DLCO). In patients who received mantle or mediastinal RT, there was a further decline in FVC following radiation therapy. At the most recent follow- up evaluation, five of 29 patients (18%) who received ABVD alone and nine of 30 (30%) who received ABVD and RT reported persistent mild pulmonary symptoms (P = .36), which did not significantly affect normal daily activity. CONCLUSION: ABVD chemotherapy induced acute pulmonary toxicity that required bleomycin dose modification in a substantial number of patients. The addition of RT resulted in a further decrease in FVC; however, this did not significantly affect the functional status of patients.